The Piro canoe. A preliminary ethnographic account - Peter Gow (Journal de la Société des Américanistes)
The Piro canoe. A preliminary ethnographic account. The article provides a preliminary account of the canoes made and used by the Piro (Yine) people of the Urubamba river in Peruvian Amazonia, with a particular focus on the processes of construction, naming and crewing. The canoe, among these people, is a basic model of affinity, both male-female and male-male. The canoe and canoe journeys are a basic social model of space for these people, serving a symbolic function that usually falls to house and village space in indigenous Amazonian societies.